The Effectiveness of Gratitude Training to Improve the Subjective Well-Being of Broken Home Adolescents in The Child Care Community (KOPA) Medan - Elvinawanty, Rianda; Jasmine, Jasmine; Harefa, Lidia Permata; Tanujaya, Marcell; Theresia, Jesslyn (Psikostudia : Jurnal Psikologi, 2022)
In this modern area, internet is very easy to be accessed, most of adolescents like to compare themselves with others. Because of comparing themselves, they are less gratitude and have low subjective well-being. The aim of this research is to prove whether gratitude training can increase the subjective well-being of broken home adolescents in the Childcare Community (KOPA) Medan. This research is experimental research with non equivalent control group design. Shapiro Wilk is used as normality test. Scale is used for data collection techniques. There are thirty adolescents who joined pre-test to see their level of subjective well-being dan it shows that 28 of adolescents have low and medium subjective well-being. Analysis technique in this research is quantitative research. The quantitative research uses non-parametric test which is Mann Whitney U Test with the help of SPSS (Statistical Product dan Service Solution) Program version of 25. The result of statistical test for Mann Whitney U Test and Wilcoxon shows that this research has Sig. value 0.002. In statistic, if Sig. value <0.05, hypothesis is accepted. Because of that, in conclusion, gratitude training has effect in increasing the subjective well-being of broken-home adolescents in Childcare Community (KOPA) in Medan. Penelitian ini memiliki tujuan yaitu untuk melihat apakah pelatihan kebersyukuran memiliki dampak untuk meningkatkan subjective well-being remaja broken home di Komunitas Peduli Anak (KOPA) Medan. Hipotesa pertama dalam penelitian ini adanya perbedaan yang signifikan pada subjective well-being remaja broken home sebelum dan sesudah diberikan pelatihan kebersyukuran, dengan asumsi subjective well-being meningkat setelah diberikan pelatihan kebersyukuran. Hipotesa kedua yaitu subjective well-being pada kelompok yang diberikan pelatihan kebersyukuran akan lebih tinggi daripada yang tidak mendapatkan pelatihan kebersyukuran pada remaja broken home di Komunitas Peduli Anak (KOPA) Medan. Penelitian ini ialah jenis penelitian eksperimen dengan non equivalent control group design. Data diperoleh melalui uji normalitas Shapiro Wilk. Teknik analisis dalam penelitian ini yaitu kuantitatif. Analisis kuantitatif menggunakan uji non parametris yaitu teknik analisis Mann Whitney U Test dengan bantuan program SPSS (Statistical Product and Service Solution) versi 25. Hasil dari uji statistik Mann Whitney U Test dan uji Wilcoxon yang telah digunakan pada penelitian ini memperoleh nilai Sig. sebesar 0.002. Secara statistik, jika nilai Sig.<0.05 maka hipotesa diterima. Oleh karena itu, berdasarkan hasil analisa tersebut kesimpulan yang diambil adalah bahwa pelatihan kebersyukuran berpengaruh untuk meningkatkan subjective well-being pada remaja broken home di Komunitas Peduli Anak (KOPA) Medan